Precipitation changes in the Mediterranean basin during the Holocene from terrestrial and marine pollen records: a model-data comparison - Peyron, Odile; Combourieu-Nebout, Nathalie; Kotthoff, Ulrich; Pross, Jörg (Climate of the past, 2017)
Climate evolution of the Mediterranean region during the Holocene exhibits strong spatial and temporal variability, which is notoriously difficult for models to reproduce. We propose here a new proxy-based climate synthesis synthesis and its comparison - at a regional (∼ 100km) level - with a regional climate model to examine (i) opposing northern and southern precipitation regimes and (ii) an east-to-west precipitation dipole during the Holocene across the Mediterranean basin. Using precipitation estimates inferred from marine and terrestrial pollen archives, we focus on the early to mid-Holocene (8000 to 6000calyrBP) and the late Holocene (4000 to 2000calyrBP), to test these hypotheses on a Mediterranean-wide scale. Special attention was given to the reconstruction of season-specific climate information, notably summer and winter precipitation. The reconstructed climatic trends corroborate the north-south partition of precipitation regimes during the Holocene. During the early Holocene, relatively wet conditions occurred in the south-central and eastern Mediterranean regions, while drier conditions prevailed from 45°N northwards. These patterns then reverse during the late Holocene. With regard to the existence of a west-east precipitation dipole during the Holocene, our results show that the strength of this dipole is strongly linked to the reconstructed seasonal parameter; early-Holocene summers show a clear east-west division, with summer precipitation having been highest in Greece and the eastern Mediterranean and lowest over Italy and the western Mediterranean. Summer precipitation in the east remained above modern values, even during the late-Holocene interval. In contrast, winter precipitation signals are less spatially coherent during the early Holocene but low precipitation is evidenced during the late Holocene. A general drying trend occurred from the early to late Holocene, particularly in the central and eastern Mediterranean. For the same time intervals, pollen-inferred precipitation estimates were compared with model outputs, based on a regional-scale downscaling (HadRM3) of a set of global climate-model simulations (HadAM3). The high-resolution detail achieved through the downscaling is intended to enable a better comparison between site-based paleo-reconstructions and gridded model data in the complex terrain of the Mediterranean; the model outputs and pollen-inferred precipitation estimates show some overall correspondence, though modeled changes are small and at the absolute margins of statistical significance. There are suggestions that the eastern Mediterranean experienced wetter summer conditions than present during the early and late Holocene; the drying trend in winter from the early to the late Holocene also appears to be simulated. The use of this high-resolution regional climate model highlights how the inherently patchy nature of climate signals and paleo-records in the Mediterranean basin may lead to local signals that are much stronger than the large-scale pattern would suggest. Nevertheless, the east-to-west division in summer precipitation seems more marked in the pollen reconstruction than in the model outputs. The footprint of the anomalies (like today, or dry winters and wet summers) has some similarities to modern analogue atmospheric circulation patterns associated with a strong westerly circulation in winter (positive Arctic Oscillation-North Atlantic Oscillation (AO-NAO)) and a weak westerly circulation in summer associated with anticyclonic blocking; however, there also remain important differences between the paleo-simulations and these analogues. The regional climate model, consistent with other global models, does not suggest an extension of the African summer monsoon into the Mediterranean. Therefore, the extent to which summer monsoonal precipitation may have existed in the southern and eastern Mediterranean during the mid-Holocene remains an outstanding question.